Circular Economy Approaches In Sustainable Engineering: A Systematic Literature Review Of Waste-To-Resource Technologies, Economic Impacts, And Policy Frameworks - Abdul Jamal; Adamu Abubakar (CV Media Inti Teknologi, 2026)
Background of Study: The global challenge of waste management and resource depletion is driven by the traditional linear